ANALISIS PERAKAUNAN ZAKAT DI MALAYSIA - Ali, Nor Aini (Jurnal Syariah, 2006)
This article examines zakat accounting in Malaysia including both consensus and non-consensus wealth. The result implies that zakat should be expanded to the non-consesus wealth. The calculation of zakat should also be revalued according to the current necessities and standard of living.